Pengaruh GDP, Ekspor Dan Investasi Terhadap Inflasi Di Lima Negara Anggota IDB - Novita; Sri Herianingrum (Jurnal Ekonomi, 2020)
The aim of this study is to find out how much influence GDP, exports and investment have on inflation in the five IDB member countries, namely Guinea, Malaysia, Indonesia, Brunei and Jordan. The results obtained by using a quantitative analysis of panel data re-salutations resulted that there was an influence of GDP, exports and investment on inflation but not significantly to these five IDB member countries. Many outlier factors also influenced one of them because the interest-free economy began to be implemented. This study wants to observe what factors influence inflation in the country of Guinea which is one of the IDB member countries that has the poorest characteristics among other countries. The results obtained using quantitative analysis methods of multiple linear regression panel data and classical assumptions produced that the three independent variables affect the dependent variable but are not significant. Where the relationship between DGP and inflation is positive, meaning that if GDP rises, inflation also rises. While the relationship between exports and investment to inflation is negative. This means that if exports rise, inflation will decrease and if investment rises, inflation will fall. So in general the government policies of the five IDB member countries must be more pro-aligned to raise the level of exports and investment in the country both foreign investment and domestic investment to help reduce the level of domestic inflation.